El desempeño electoral de Morena (2015-2016) - Espinoza Toledo, Ricardo; Navarrete Vela, Juan Pablo (Intersticios Sociales, 2018)
El texto analiza la irrupción de Morena en las elecciones de 2015 y 2016. Evalúa los resultados en tres ámbitos de competencia: diputados federales, en la Ciudad de México y 21 procesos electorales para renovar gobernadores. A través de diferentes indicadores se mide la atracción de votos de Morena por medio de los porcentajes de votos y se contrasta con el Coeficiente de Desempeño Electoral (CDE) para analizar, precisamente, su presencia electoral. El artículo también clasifica el nivel de competitividad en las elecciones de ambos años por medio del Índice Compuesto de Competitividad (ICC). Aunque se trata de un partido que en 2015 participó en su primera competencia política, los resultados permiten ubicar sus avances en la CDMX y observar los retos organizativos que tiene en el resto del país. The electoral performance of MORENA (2015-2016) This text analyzes the incursion of a new political party –MORENA– in elections in Mexico in 2015 and 2016, by evaluating results in three areas of government: federal congressmen, representatives in Mexico City, and gubernatorial processes in 21 states. Using a series of indicators, MORENA’S appeal to voters is measured by the percentage of ballots cast in its favor. Our results are then contrasted to the formal Electoral Performance Coefficient (CDE) in order to determine more precisely this party’s electoral presence. The article also classifies the level of competitiveness in the elections in both years by means of the Competitive Composite Index (ICC). Although 2015 marked the first occasion in which MORENA participated in political competition, results allow us to ascertain its advances in Mexico City and observe the organizational challenges it faces in the rest of the country. Keywords: MORENA, ICC, CDE, competitiveness